The Canva Tool as A Strategy and Its Relationship with Significant Learning - Thais Milagros Tovar Gaspar; Javier Jesús Oliva Gamarra; Jesús Pol Vicente Lopez; Fausto Cesar Sarmiento Janampa; Miguel Angel Alania Vasquez; Cristhian Ovidio Ramírez-Valladares; Olga Giovanna Cuadros Serna (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The objective of the research is to determine the application of the canva tool as a strategy in the development of meaningful learning in the students of the VIII cycle of studies of the school of education of the Los Angeles de Chimbote University, Ancash-2023. The methodology was quantitative type, descriptive-correlational level and the design was non-experimental, as a technique the survey has been considered and the instrument was the questionnaire which has been validated by expert judgment. The sample has been considered 40 students in which it has been chosen using the convenience sampling technique. Results: It was verified that the canva tool is related to motivation in the development of significant learning, reaching a correlation value of 0.788, meaning a very strong positive correlation level. It was found that the canva tool is related to functionality and interest in the development of meaningful learning, with a value of 0.735, corresponding to a very strong positive correlation level. Likewise, the canva tool is related to active participation in the development of meaningful learning, reaching a correlation value of 0.852, corresponding to a positive correlation level of very strong magnitude. Finally, it was concluded that: the level of correlation between the application of the canva tool as a strategy in the development of significant learning in the students of the VIII cycle of education studies was 0.682, thus corresponding to a significantly strong positive correlation.